Streptomyces sp. Sebagai Biofungisida Patogen Fusarium oxysporum (Schlecht.) f.sp. lycopersici (Sacc.) Snyd. et Hans. Penyebab Penyakit Layu Pada Tanaman Tomat (Solanum lycopersicum L.) - SARI, NURI MANDAN; KAWURI, RETNO; KHALIMI, KHAMDAN (Agrotrop : Journal on Agriculture Science; Vol 2 No 2 (2012), 2014)
A research was conducted to isolate Streptomyces sp. of soil Udayana University campus in the Bukit-Jimbaran, to obtain the most effective Streptomyces sp. which is effective in inhibit the growth of Fusarium oxysporum f.sp. lycopersici, and to test response of tomato plants with Streptomyces sp. culture against Fusarium wilt desease. Implementation phases of the research consisted of isolation and identification of Streptomyces sp, test the inhibition against F. oxysporum f.sp. lycopersici, and in vivo test used by dyeing the roots of the tomato plant (Solanum lycopersicum) with Fusarium spores and after 30 seconds the roots were dyeing Streptomyces culture. Furthermore, sterile soil in polybag watered by Fusarium spores and Streptomyces culture at the same time. Based on morphological characteristic it found five isolates of Streptomyces sp.. The antagonist test showed Streptomyces sp. 1 had ability (75%) against Fusarium, Streptomyces sp 2 (68,3%), Streptomyces sp. 3 (71,6%), Streptomyces sp. 4 (63,3%), and Streptomyces sp. 5 (21,6%). All Streptomyces suppressed the growth of Fusarium on tomato plants in glass house (p<0,05). Streptomyces sp.3 suppressed Fusarium wilt disease in tomato from 88% in control to 20%.
Keywords: Streptomyces sp, Fusarium oxysporum f.sp. lycopersici, Solanum lycopersicum, biofungicide